KONSTRUKSI MAKNA PESAN PADA PEMBERTITAAN JOKOWI RESMI MENJADI PEMILIH PEMILU 2024 PADA MEDIA CNN INDONESIA DAN LIPUTAN6.COM - Hendrawan, M (SCIENTIA JOURNAL, 2024)
Mass media is a component that cannot be ignored in human efforts to find the latest news. Media alwayshas a goal when conveying information, including political, ideological or commercial goals. To achieve thisgoal, the media often manipulates the news in a way that can influence readers' opinions to fit the desirednarrative, using framing techniques as described by Robert N. and Entman. Framing theory is often used toinfluence readers' opinions. Robert N. and Entman emphasize framing theory, focusing on certain aspects ofthe news to form a specific view. This research uses qualitative methodology, specifically Robert N.Entman's analytical framework, to describe the phenomenon in the news about Jokowi being registered as avoter for the 2024 Election on Cnnindonesia.Com and Liputan6.Com. Research objects include focus, timeand place of research, providing an overview and being the target of data and information. Choosing the rightresearch object is important for determining the focus of the research, including factors that influence andbecome issues of the research subject itself.